EFL Learner's Experience of Zoom Platform use in Online Research Consultation During COVID-19 - Anggita, Ayu (AL LUGHAWIYAAT, 2022)
This qualitative study aims to explore EFL learners’ experience of Zoom platform use in online research consultation during COVID-19. Data were gathered from five students' reflection who used Zoom platform as a media for online research consultation during the COVID-19 pandemic. Framed by usability concept, findings of the study reveal that in terms of learnability, Zoom platform facilitates the senior students in their online consultation process. Meanwhile, in terms of satisfaction, findings reveal that students were satisfied with the use of Zoom due to feature support in the platform.